NIOSH pocket guide to chemical hazards (U.S. Dept. of Health and Human Services, Public Health Service, Centers for Disease Control and Prevention, National Institute for Occupational Safety and Health ; For sale by the Supt. of Docs., U.S. G.P.O., 2007)
This 2007 publication is intended as a source of general industrial hygiene information on several hundred chemicals/classes for workers, employers, and occupational health professionals. It does not contain an analysis of all pertinent data, rather it presents key information and data in abbreviated or tabular form for chemicals or substance groupings (e.g. cyanides, fluorides, manganese compounds) that are found in the work environment. The information found in this Guide should help users recognize and control occupational chemical hazards.
Keywords: Hazardous substances -- Handbooks, manuals, etc.; Chemicals -- Safety measures -- Handbooks, manuals, etc.; Industrial toxicology -- Handbooks, manuals, etc.; Hazardous substances -- Safety measures -- Handbooks, manuals, etc.; Hazardous substances -- United States -- Safety measures.; Toxicology.; elektronické knihy; electronic books